Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Take the function

$f(x) = \sin(2x) \cdot \cos(x)$

Find the 2013 th derivative

What I have found so far:

$f''(x)= -4\sin(x) \cdot \cos(2x) - 5f(x)$

I am assuming I need to find a relationship such as the above in order to just apply it again and again, however I can't seem to do so.

Any help is appreciated. Thank You.

=============================

EDIT: @Ihsan and Babak

Utilising this result, results in:

$f''(x) = -8\sin(3x) - f(x) $

And I'm not sure how to make recur this 1006 times!

share|improve this question
3  
Use the hints of Ihsan/Babak and the fact that $f(x)=g(x)+h(x)$ implies $f^{(n)}(x)=g^{(n)}(x)+h^{(n)}(x)$. –  Hagen von Eitzen Feb 11 '13 at 10:35
    
Now note that $\frac {d^4}{dx^4} \sin (ax) = a^4 \sin (ax)$ –  Ross Millikan Feb 11 '13 at 19:33

4 Answers 4

$$2\sin(2x)\cos(x)=\sin(3x)+\sin(x)$$ Use this.

share|improve this answer
    
edited my post. –  Sy123 Feb 11 '13 at 10:30

Hint: Use $$\sin\alpha\cos β= \frac{1}2[\sin (\alpha + β) + \sin (\alpha − β)]$$ and $$\sin^{(n)}(x)=\frac{d^n}{dx^n}\sin(x)=\sin(x+\frac {\pi}{2}n)$$ and use the Chain rule also.

share|improve this answer
    
edited my post. –  Sy123 Feb 11 '13 at 10:30
    
@Sy123: Do you want $f''(x)= -4\sin(x) \cdot \cos(2x) - 5f(x)$ becomes $f''(x) = -8\sin(3x) - f(x) $ above?? –  Babak S. Feb 11 '13 at 10:35
    
Thank you, that really helped. (the nth derivative bit) –  Sy123 Feb 11 '13 at 10:36
    
Your guidance is helpful! +1 –  amWhy Feb 11 '13 at 17:36

Hint: Try to express the function using $e^x$ using: $\sin(\alpha) = \frac{e^{i \alpha} + e^{i\alpha}}{2i}$ and $\cos (\alpha) = \frac{e^{i\alpha}+e^{-i\alpha}}{2}$.

Full solution: (up to minor errors, if any...) $$ \sin(2x) \cos(x) =\left(\frac{e^{i2x}-e^{-i2x}}{2i} \right)\left(\frac{e^{ix}+e^{-ix}}{2} \right)=\frac{1}{4i}(e^{i3x}-e^{-i3x}+e^{ix}-e^{-ix}). $$ Since $(e^{ax})'=ae^{ax}$, the $2013$-th derivative is $$ (e^{ax})^{[2013]}=a^{2013}e^{ax}. $$ Plugging this to the former equation and recalling that $i^{2013}=i^{2012}i=1^{503}i=i$, we get $$ \begin{array}{lll} (\sin(2x) \cos(x))^{[2013]}&=&\left(\frac{1}{4i}(e^{i3x}-e^{-i3x}+e^{ix}-e^{-ix})\right)^{[2013]}\\ &=&\frac{1}{4i} \big((i3)^{2013} e^{i3x}- (-i3)^{2013}e^{-i3x}+(i)^{2013} e^{ix}- (-i)^{2013}e^{-ix}\big)\\ &=&\frac{i}{4i}\big( 3^{2013}(e^{i3x}+e^{-i3x}) + e^{ix}+e^{-ix}\big)\\ &=&\frac{3^{2013}}{2}\frac{e^{i3x}+e^{-i3x}}{2} +\frac{1}{2}\frac{e^{ix}+e^{-ix}}{2}\\\ &=&\frac{3^{2013}}{2}\cos 3x+\frac{\cos x}{2}. \end{array} $$

share|improve this answer

Note the 2nd derivative of $\sin(a x)$ is $-a^2 \sin (a x)$ (and similar for $\cos a x)$ that is $\frac{d^2}{dx^2} f(a x) = -a^2 f(a x)$ when $f(x)$ is sine or cosine. Doing two more derivatives you find the 4th derivative is $a^4 \sin( a x)$. Repeating this four more times, you get the 8th derivative is $a^8 \sin (a x)$ as eight is a multiple of 4. (Similarly 2012 is a multiple of 4; and then you have to do one more derivative to get to the 2013th derivative).

It helps to use trigonometric formulas to break the product of two trig functions into the sum of trig functions.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.